Interannual variability in the transport of fish eggs in the Kattegat and Öresund - Pacariz, Selma; Björk, Göran; Svedäng, Henrik (ICES Journal of Marine Science, 2014)
The dispersal and retention of early life stages are essential factors for the recruitment of fish stocks, and often depend on local meteorological and hydrographical conditions. A BAltic sea Long-Term large Scale Eutrophication Model (BALTSEM) was used to examine interannual variation in the retention and dispersal of fish eggs, Atlantic cod (Gadus morhua) at spawning areas in the Kattegat and Öresund and to investigate the mechanisms responsible for this variation. Model simulations over period 1971–2006 showed that years with high retention were related to variable weak winds and a strong outflow of water from the Baltic Sea, while years with low retention were related to strong westerly winds. Low egg retention was associated with enhanced southward transport from the Kattegat towards the Great Belt and from the Öresund towards the Baltic Sea. This southward transport of eggs was highly correlated with the local westerly wind component. The southbound egg transport and the westerly wind component both increased after 1989, and were connected with a change in the large-scale atmospheric circulation pattern, as represented by the NAO index. Results of this study provide information about the connectivity between neighboring areas and suggest that sedimentation is an important mortality factor.